2014
DOI: 10.1179/1607845414y.0000000205
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dickkopf-1 levels in chronic lymphocytic leukemia and increased osteopontin levels in non-Hodgkin's lymphoma at initial diagnosis: Could they be playing roles in pathogenesis?

Abstract: Aims We determined plasma levels of dickkopf-1 (DKK-1) and osteopontin (OPN) which have roles in the Wnt pathway in chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma (NHL) patients and in healthy controls. We also tested whether DKK-1 and OPN levels could be of clinical or prognostic significance in CLL and NHL. Methods We included 36 CLL, 24 NHL patients, and 21 healthy controls. Patients' clinical and demographic features, treatment modalities, and response to treatment were recorded. DKK-1 and OPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We also found that DKK-1 is highly expressed in HpSC-HCC and presented it as a novel biomarker that regulates Wnt signaling [ 18 , 19 ]. DKK-1 expression has also been reported to be elevated in HCC tissues [ 20 ], and DKK-1 is dysregulated in various other malignant tumors, such as pancreatic cancer, colorectal cancer, multiple myeloma, and chronic lymphocytic leukemia [ 21 , 22 , 23 , 24 ]. The diagnostic value of serum DKK-1 levels for HCC has previously been determined [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that DKK-1 is highly expressed in HpSC-HCC and presented it as a novel biomarker that regulates Wnt signaling [ 18 , 19 ]. DKK-1 expression has also been reported to be elevated in HCC tissues [ 20 ], and DKK-1 is dysregulated in various other malignant tumors, such as pancreatic cancer, colorectal cancer, multiple myeloma, and chronic lymphocytic leukemia [ 21 , 22 , 23 , 24 ]. The diagnostic value of serum DKK-1 levels for HCC has previously been determined [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…An association between the expression of osteopontin and extranodal disease has been also reported. 27 OPN has been linked to the tropism of neoplastic B cells to the central nervous system (CNS) and it has been found that the OPN gene is up-regulated in the primary nervous system lymphoma. 28-30 Although the characteristics of our study do not allow us to identify a relationship between OPN expression and CNS involvement by lymphoma, we consider that it is important to deepen the investigations to know if the expression of OPN in the neoplastic cell can predict an infiltration, posterior to the central nervous system, as it would help to discern which patients with DLBCL would benefit from prophylaxis to prevent CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies have demonstrated that the expression of DKK-1 is downregulated in colorectal adenoma carcinoma at late CRC stages (33). DKK-1 has also been revealed to be downregulated in chronic lymphocytic leukemia and papillary thyroid cancer (34,35). The current study predicted binding between miR-410 and DKK-1 using bioinformatics methods and then confirmed this interaction by luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%